Pediatric Lipoblastoma: A Case Report in a 2-year-old Girl - Amar Shah; Ria Sharma; Anirudh Shah (Journal of Indian Association of Pediatric Surgeons)
Adipose tumors constitute only 6% of all soft-tissue neoplasms in the first two decades of life, with lipoblastomas accounting for one-third of these cases. Predominantly seen in children under 3 years old, preoperative diagnosis is challenging due to their heterogeneity and similarity to other lipomatous tumors. Surgical excision and histology remain essential for definitive diagnosis. We report the case of a 2-year-old girl with a right infraclavicular lipoblastoma.